Determinants of Employee Performance at Matahari Department Store Arion Mall Based on Loyalty and Demographics - Sealviana Candra Marisa; Ari Apriani (Lembaga Riset dan Inovasi Al-Matani, 2023)
During the Covid-19 pandemic, Matahari Department Store Arion Mall has ups and downs in its development, employees are required to work harder and smarter to be able to increase company sales. This company annually conducts a Performance Appraisal to assess the performance of its employees. The condition in 2023 recorded 98.5% of its employees obtained results less than expectations. The average tenure of employees in this store is >5 years, generally employees with a long tenure have good loyalty and can make a positive contribution. Generally, the most gender is female, because the company is engaged in retail that sells fashion products, so they tend to hire women because of their neatness and character. While the most age is classified as mature, in this age range often has more work experience, so it is assumed that it can contribute effectively. The population of this study are employees at Matahari Department Store Arion Mall, namely grade 1 permanent employees as many as 67 people, so the sampling technique uses saturated samples. This study used a questionnaire with a Likert scale for data collection and quantitative analysis using the SPSS version 25 analysis tool. The results of this study indicate that although tenure has no effect on employee performance, other variables such as loyalty, gender, and age have a positive and significant effect.